Leadership Styles of Faculty Members at Faculty of Science at Taibah University and its Relationship to Students’ Motivation towards Learning Science - Al-Zayde, Daifallah Bin Awad; Raid Anagreh, Hazem (Dirasat: Educational Sciences, 2020)
This study aims to investigate the relationship between leadership styles among faculty members at the Faculty of Science at Taibah University and its relationship to students’ motivation towards learning science. To achieve this goal, a questionnaire was built to identify leadership styles, and another questionnaire was developed (Tuan, Chin, and Shieh, 2005) to measure motivation towards learning science. They were applied to a sample of (543) male and female students, using a correlative descriptive approach. The results showed that the democratic style is the most prevalent among faculty members, and that the level of students’ motivation towards learning science was moderate. The results also revealed the existence of a correlation at the significance level (α ≤ 0.05) between the democratic style and students’ motivation towards learning science. In view of the results of the study, the researchers recommend the intensification of training courses and workshops for faculty members about the various leadership styles and the way to practice the appropriate leadership style according to the instructional situation.